Tornado Hazard Assessment for a Nuclear Power Plant in China. (September 2017) - Zhu, Hao; Chen, Jiayi; Li, Fengju; Bai, Xiaoping; Wang, Xiaoliang; Wang, Hongyu; Zheng, Wei
Abstract: Tornado is one of the most hazardous external natural events which should be taken into account in the siting, design and safety evaluation of nuclear power plants. The tornado hazard has been assessed for a nuclear power plant located in the Southeast China in this paper. Using the original Fujita scale and grading by a number of experts, intensities of the tornado segments have been determined. The design-basis tornado wind speed, parameters and missiles generated have been evaluated following the methodology listed in the hChinese Nuclear Safety Guide HAD101/10. The results show that the overall cumulative frequency and intensity of tornadoes in the site area is not in a logarithm-linear relationship. The expected annual tornado occurrence frequencies of various F scales have been estimated by fitting higher intensity samples. The resulting wind speed corresponding to an exceedance frequency of 10 -7 per year seems to be sensitive to the fitting samples. Considering the uncertainties, the intensity and frequency of tornadoes in the survey area, the ultimate design-basis tornado wind speed is taken to be 70.4 m/s, which is the lower limit wind speed of F3 scale. Moreover current problems in tornado hazard assessment in China are discussed.